Die Kareze in Afghanistan - Jentsch, Christoph (ERDKUNDE, 1970)
Karezes, the ingenious water transport system of the Iranian Highland, also occur widely in the Kingdom of Afghanistan. The appearance of the maps of the Afghanistan topographic survey over the past few years has made it possible to precisely define and analyse the distribution of these installations. In places signs that the system is collapsing can be seen, spurred on by the spread of water pumping. The Karezes of Afghanistan differ from those of central Iran in minor details of construction and in their shorter length. As Cressey, however, has reported from Iran, successions of these installations within an oasis are very common. The construction of Karezes is also influenced by relief. In irrigation, agricultural practice must have regard to the particular characteristics of the local ground water. The water yield of the bored groundwater layer varies within fairly tight limits of 20 to 60 litres per second. In consequence, the scattered Karezes-irrigated oases exhibit a uniformity, indeed a monotony, which allows one to speak of a typical agricultural landscape of Karezes irrigation. The Karezes in Afghanistan lie mainly in the communal ownership of the villages, so that their operation and maintenance form part of the common duties of the rural population. The Karezes are found in the entire highland area south and west of the Hindu Kush but there is an especially marked concentration on the eastern plateau. Karezes are lacking on the north side of the Hindu Kush mountain system. The explanations of this one-sided distribution appear to lie less in natural conditions - the salinisation danger is general - as more in the ethnic groupings of the population. Estimates of the agricultural land area of the country indicate that almost one-fifth of irrigated land receives water only through Karezes, which underlines the continuing importance of this water retrieval system.